DAMPAK ALIH FUNGSI LAHAN TERHADAP KETAHANAN EKONOMI RUMAH TANGGA PETANI DI DESA-DESA SEKITAR KAWASAN NUSA DUA - I Made Sujana; Ni Luh Wulani Parwati; Putu Ratna Windusara Putri; Anak Agung Istri Setiari JMH (Yayasan Nusantara Hasana Berdikari, 2022)
The rapid development of the tourism sector in the Nusa Dua area, Badung Regency, Bali, has accelerated the conversion of agricultural land into residential, tourism accommodation, commercial, and service areas. This phenomenon has generated complex impacts on the socio-economic conditions of farmer households in villages surrounding Nusa Dua. This study aims to analyze the impact of land use conversion on the economic resilience of farmer households, identify the driving factors behind land conversion, and examine adaptation strategies employed by farmer households to sustain their livelihoods. The research applies a descriptive qualitative approach supported by quantitative data collected through in-depth interviews, field observations, and documentation. The findings indicate that land conversion has reduced productive agricultural land, decreased the contribution of agriculture to household income, and increased dependence on non-agricultural sectors, particularly tourism. Nevertheless, several farmer households have improved their economic resilience through livelihood diversification, small business investments, and employment opportunities in the tourism service sector. This study concludes that land conversion simultaneously produces both positive and negative effects on the economic resilience of farmer households. Therefore, sustainable land conversion control policies and local economic empowerment programs are required to ensure balanced regional development.